2009
DOI: 10.1101/gr.086827.108
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of gene function and regulatory control after whole-genome duplication: Comparative analyses in vertebrates

Abstract: The significance of whole-genome duplications (WGD) for vertebrate evolution remains controversial, in part because the mechanisms by which WGD contributed to functional evolution or speciation are still incompletely characterized. Fish genomes provide an ideal context in which to examine the consequences of WGD, because the teleost lineage experienced an additional WGD soon after divergence from tetrapods and because five teleost genomes are available for comparative analysis. Here we present an integrated ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
161
2
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 184 publications
(176 citation statements)
references
References 62 publications
11
161
2
1
Order By: Relevance
“…This is roughly in agreement with the first genome-wide, comparative analysis of five different fish species by Kassahn et al (Kassahn et al, 2009) These authors found that in all five species examined, 3-4% of the genes show strong evidence for having originated in the ancient TS-WGD. Due to the design of the study, this number is probably underestimating the real abundance of gene retention after TS-WGD, and can be considered a minimum estimate, as pointed out by the authors themselves.…”
Section: Non-functionalizationsupporting
confidence: 79%
“…This is roughly in agreement with the first genome-wide, comparative analysis of five different fish species by Kassahn et al (Kassahn et al, 2009) These authors found that in all five species examined, 3-4% of the genes show strong evidence for having originated in the ancient TS-WGD. Due to the design of the study, this number is probably underestimating the real abundance of gene retention after TS-WGD, and can be considered a minimum estimate, as pointed out by the authors themselves.…”
Section: Non-functionalizationsupporting
confidence: 79%
“…The reason is that distributed genomic networks can undergo rapid modification and come to adopt encode novel functions without loss of the original functionality. This potential has contributed to the adaptation of signal transduction and other multicomponent systems to diverse cell and developmental functionalities [142][143][144][145].…”
Section: Protein Family and Network Amplificationmentioning
confidence: 99%
“…Given that the expression data employed for sorghum and maize were measured by ESTs, the observed subfunctionalization of gene expression should be treated with caution, and further analyses are needed. In a recent study, analyses of vertebrate WGD events showed that about 24% of the ohnologs encoded proteins that differed in domain architecture and/or subcellular localization (Kassahn et al, 2009). The usefulness of this analysis would be helpful to detect signatures of subfunctionalization at the sequence level without the lack of functional data or protein structure in many of our analyzed genomes and data sets.…”
Section: Functional Classes Of Wgd Retained Genesmentioning
confidence: 99%
“…Sémon and Wolfe (2008) suggested that subfunctionalization might play a prevalent role in both the initial preservation and long-term evolution of WGD duplicated genes. Another recent study with several vertebrate genomes supported that neofunctionalization is more prevalent (Kassahn et al, 2009). However, Freeling (2008, 2009) argued that if subfunctionalization or neofunctionalization was dominant after WGDs, then functional classes overretained for WGD duplicates might also be enriched for duplicates derived from SSDs, due to the similar evolutionary forces operating on them.…”
mentioning
confidence: 99%
See 1 more Smart Citation